2020
DOI: 10.1016/j.tifs.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Naturally enhanced eggs as a source of vitamin D: A review

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 83 publications
(115 reference statements)
2
21
0
Order By: Relevance
“…A research study showed an increase in vitD3 for eggs from free-range hens given accessibility to the sun (37). In a review, data produced for food composition tables by an LC-MS/MS method showed a content per 100 g ranging from 0.92-2.5 µg vitD3 and 0.13-1.0 µg 25-OHD3 (12). Thus our results are within this interval.…”
Section: Content Of Vitamin D Metabolites In Foodssupporting
confidence: 72%
See 4 more Smart Citations
“…A research study showed an increase in vitD3 for eggs from free-range hens given accessibility to the sun (37). In a review, data produced for food composition tables by an LC-MS/MS method showed a content per 100 g ranging from 0.92-2.5 µg vitD3 and 0.13-1.0 µg 25-OHD3 (12). Thus our results are within this interval.…”
Section: Content Of Vitamin D Metabolites In Foodssupporting
confidence: 72%
“…The update include milk, dairy products, broiler, and pork products (11,12,15,35) This article is protected by copyright. All rights reserved.…”
Section: Quantification Of Fatmentioning
confidence: 99%
See 3 more Smart Citations